Statistical analysis of technical specifications for non-reversible plate vibrators with different types of engines - M. A. Afanasev; I. S. Tyuremnov (Вестник СибАДИ)
Introduction. Forward plate compactors are surface soil compaction machines with a flat operating device, which are usually equipped with a single-shaft vibration exciter. Forward plate compactors may be driven by gasoline, diesel or electric engines. When designing and modernizing forward plate compactors, a problem of technical specifications justification may arise, including such parameters as exciting force, vibration exciter oscillation frequency, engine power, base plate width, etc. This statistical analysis of plate compactors with different types of engines was carried out to summarize manufacturers practices and reveal correlations between the technical specifications of forward plate compactors.Materials and methods. This research is based on the information presented on the official websites of forward plate compactors manufacturers and their dealers. 644 models of forward plate compactors were scrutinized. Regression equations and correlation coefficients were derived using Microsoft Excel software.Results. Parameters ranges for forward plate compactors with different types of engines were determined. Regression equations of correlations between oscillation frequency, exciting force, engine power, base plate width, relative exciting force and mass of forward plate compactors with different types of engines were derived, as well as the corresponding correlation coefficients. It was revealed, that most parameters have low or very low correlation coefficient, regardless of the engine type.Conclusion. The ranges of the technical specifications of diesel and gasoline forward plate compactors are quite close to each other. The parameters ranges of electric plate compactors, in most cases, are beyond the ranges of gasoline and diesel plate compactors. Low correlation coefficients and a large scatter of parameters indicate that manufacturers do not have a methodology for justification of the technical specifications of forward plate compactors. Results of the study may be used when clarify ranges of parameters and formulate requirements for a mathematical model of vibration plates behavior.